The Role of Strategic Leadership in the Implementation of TQM in Cameroonian Hospitals - Marvin Nso, Eyong-Echaw (Digital Repository of Theses - SSBM Geneva, 2025)
Recent studies show that the healthcare sector is experiencing great desire towards quality improvements through effective quality management in order to assist in service quality and patients/clients satisfaction. The role of strategic leaders in the implementation of TQM within Cameroonian hospitals cannot be overemphasized. The purpose of this qualitative study was to gain a deeper understanding on how TQM protocols are planned, aligned and implemented in the state hospitals in Cameroon. To assess subjective data to gain a detailed understanding of the variables involved, the qualitative research was conducted through semi-structure interviews with 21 study participants from seven state hospitals. Hospitals and participants were purposively selected. In addition to semi-structured interviews, the data was collected using content analysis of secondary data (relevant literature and the study hospitals’ documentation). The analysis of this data was done with qualitative analysis tools and software (Atlas-TI). The study findings clearly indicated that all Cameroonian state hospitals have to develop a patient-centered approach to healthcare and service delivery, effectively manage personnel non-complaints, perform regular monitoring and patient need assessment, effectively implement the TQM philosophy through promoting of a work culture of quality, establishment of innovations that favour TQM implementation, ensure coordination, monitoring and personnel motivation while presenting themselves as good examples to instill personnel commitment and a work culture of quality through effective TQM implementation. Future research was recommended to be performed in varying areas like, The impact of TQM on operation performance in Cameroonian hospitals, The role of strategic leadership in the implementation of TQM in the Cameroonian private hospitals and an analysis of the relationship between Strategic leadership and TQM in the Cameroonian hospitals. Keywords: Strategic leadership, Total quality management, State hospitals, Cameroon.